High-Temperature Low-Cycle Fatigue Behaviour of MAR-M247 Coated with Newly Developed Thermal and Environmental Barrier Coating - Ivo Šulák; Karel Obrtlík; Ladislav Čelko; Pavel Gejdoš; David Jech (Advances in Materials Science and Engineering)
This study investigates the strain-controlled low-cycle fatigue (LCF) behaviour of an untreated and surface-treated MAR-M247 superalloy in a symmetrical push-pull cycle with a constant strain rate at 900°C in laboratory air. A newly developed experimental thermal and environmental barrier coating (TEBC) system, consisting of a 170 μm thick CoNiCrAlY bond coat (BC) and a bilayer ceramic top coat (TC), with an interlayer and an upper layer, was deposited using air plasma spray techniques. The ceramic interlayer with an average thickness of 77 μm was formed from agglomerated and sintered yttria-stabilized zirconia. An experimental mixture of mullite (Al6Si2O13) and hexacelsian (BaAl2Si2O8) at a ratio of 70/30 vol.% was sprayed as the upper layer. The average thickness of the TC was 244 μm. The specimen sections were investigated using a TESCAN Lyra3 XMU scanning electron microscope (SEM) to characterise the microstructure of both the TEBC and the substrate material. The fatigue damage mechanisms in the TEBC-coated superalloy were studied. The fatigue life curves in the representation of the total strain amplitude versus the number of cycles to failure of the TEBC-coated and uncoated superalloy were assessed. TEBC was found to have a slight, positive effect on the fatigue life of MAR-M247.